2011
DOI: 10.1016/j.chemosphere.2011.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Powdered activated carbon coupled with enhanced coagulation for natural organic matter removal and disinfection by-product control: Application in a Western Australian water treatment plant

Abstract: The removal of organic precursors of disinfection by-products (DBPs), i.e. natural organic matter (NOM), prior to disinfection and distribution is considered as the most effective approach to minimise the formation of DBPs. This study investigated the impact of the addition of powdered activated carbon (PAC) to an enhanced coagulation treatment process at an existing water treatment plant on the efficiency of NOM removal, the disinfection behaviour of the treated water, and the water quality in the distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 21 publications
3
47
1
3
Order By: Relevance
“…The concentrations of these DBP precursors should therefore be kept to a minimum at the point of water disinfection and thereafter (Richardson et al, 2003;Trofe et al, 1980). DBP precursor removal has traditionally focussed on NOM removal, with water treatment methods such as enhanced coagulation (EC) and powdered activated carbon (PAC) adsorption widely used for this purpose (Kristiana et al, 2011). These treatments, however, do not remove halides (Sigworth and Smith, 1972), therefore they increase the bromide to dissolved organic carbon (Br:DOC) ratio and can preferentially form brominated DBPs when bromide is present in sufficient concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of these DBP precursors should therefore be kept to a minimum at the point of water disinfection and thereafter (Richardson et al, 2003;Trofe et al, 1980). DBP precursor removal has traditionally focussed on NOM removal, with water treatment methods such as enhanced coagulation (EC) and powdered activated carbon (PAC) adsorption widely used for this purpose (Kristiana et al, 2011). These treatments, however, do not remove halides (Sigworth and Smith, 1972), therefore they increase the bromide to dissolved organic carbon (Br:DOC) ratio and can preferentially form brominated DBPs when bromide is present in sufficient concentration.…”
Section: Introductionmentioning
confidence: 99%
“…PAC is also usually used as an emergency measure to remove algae, taste and odor compounds and other pollutants in raw water with high concentration (Westerhoff et al, 2005;Zhang et al, 2010). Previous studies have reported that PM oxidation or PAC adsorption can reduce and/or increase the formation of several regulated C-DBPs and unregulated N-DBPs by removing and/or chemically transforming precursors prior to disinfection (Chen and Valentine, 2008;Chu et al, 2011;Kristiana et al, 2011;Jiang et al, 2014). However, very little information is available concerning the control of a range of N-DBPs in N-rich waters pre-treated by coupling PM oxidation and PAC adsorption (PM-PAC).…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon is used as adsorbent [13][14][15][16] in some combined coagulation-flocculation/ adsorption treatment systems. However, activated carbon is cost prohibitive and neither the regeneration nor the disposal of used carbon is straightforward.…”
Section: Introductionmentioning
confidence: 99%